Experimental Evaluation of the Effect of Fiber Type on Mechanical Properties of Concrete - Sparsh Kumar,; Dr. T.N. Mishra, (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
Concrete is inherently strong in compression but weak in tension, leading to brittle failure and crack propagation under service loads. Fiber Reinforced Concrete (FRC) has been developed to address these limitations through the inclusion of discrete fibers that enhance mechanical performance. The present study experimentally evaluates the effect of different fiber types on the mechanical properties of concrete, with specific emphasis on compressive and flexural strength. Steel fibers and synthetic fibers were incorporated into M25, M30, and M40 grade concrete mixes in controlled proportions. Standard laboratory tests were conducted to assess workability, compressive strength at 7 and 28 days, and flexural strength at 28 days. The results demonstrate that while fiber inclusion has a marginal effect on compressive strength, it significantly improves flexural strength, ductility, and post-cracking behavior. Steel fiber reinforced concrete exhibited superior performance compared to synthetic fiber reinforced concrete, particularly in flexural strength enhancement and crack control. The findings confirm that fiber type plays a critical role in determining the mechanical performance of Fiber Reinforced Concrete and supports its application in structural and pavement engineering.
Keywords: Fiber Reinforced Concrete; Steel Fibers; Synthetic Fibers; Compressive Strength; Flexural Strength; Mechanical Properties